58 Assessing and managing constipation for patients receiving palliative care in a hospice setting: a systematic review of the literature. Issue 3 (1st September 2017) - McIlfatrick, Sonja; Preshaw, Deborah; Hasson, Felicity; Carduff, Emma; Clarke, Mike; Coast, Jo; Ferguson, Claire; Finucane, Anne; Graham, Lisa; Larkin, Philip; McCorry, Noleen; Slater, Paul; et al.
Abstract : Introduction: Constipation causes considerable suffering, either as a direct result of physical symptoms or due to related social and psychological problems. Despite this, uncertainty persists about the best management within hospice settings. Aim: To synthesise the current evidence base on the assessment and management of constipation for palliative care patients within a hospice setting. Methods: A systematic search of MEDLINE, Embase, Cinahl, Scopus, and Cochrane databases was undertaken in April 2017 for empirical studies, written in English, on the assessment and management of constipation in the hospice, between 2007 and 2017. Two researchers independently reviewed and critically appraised all studies, conducted data extraction and undertook a thematic analysis. Results: Fourteen studies were included in the review including randomised trials (n=3), observational (n=5), and descriptive studies (n=6). The majority of the research was conducted in palliative care units and targeted either healthcare professionals or patients. The analysis highlighted a lack of standard definition of constipation. Clinicians experienced challenges in constipation assessment, with a need to combine patient reports with physical examination. Clinicians focused on pharmacological management, however, consideration around non-pharmacological aspects is also essential. Finally, the need to assess current practice for the management of constipation in light of changing priorities of care at end of life was emphasised. Discussion: Supporting clinicians to more effectively assess and manage the complexities of constipation in this setting is essential in improving overall symptom management. Gaps in the evidence base included defining constipation, constipation prevention, non-pharmacological management, and management in the dying patient.